Penerapan Arsitektur Organik Pada Pusat Pelatihan Musik Di Kota Makassar - Sasa Margapita; Marwati, Marwati; Herniwati, Andi (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_ The Music Training Center is a place that accommodates all activities related to one's expression in music, which accommodates teaching and learning activities about rhythms, songs, and features produced by the human voice or musical instruments that can make sounds. Several types of music known in Makassar will be implemented at the Music Training Center, namely traditional and modern music. The purpose of this writing is to design a Music Training Center using the concept of organic architecture with Frank Lloyd Wright's principles, namely Building as nature, Continuous present, Form Follows Flow, Of the people, and Of the materials which are located on Jalan Tanjung Bunga, Makassar City. The discussion method begins with data collection, processing through analysis and data synthesis, and then processing into a design concept. Collecting data using a qualitative descriptive method. The design results include applying organic architecture to the form and appearance of building facades and interiors and using several physical attributes of the environment so that buildings can appreciate nature more, blend with nature, and be in harmony with their environment.